2013
DOI: 10.1007/s40037-013-0079-7
|View full text |Cite
|
Sign up to set email alerts
|

An integrated model for developing research skills in an undergraduate medical curriculum: appraisal of an approach using student selected components

Abstract: Student selected components (SSCs), at that time termed special study modules, were arguably the most innovative element in Tomorrow’s Doctors (1993), the document from the General Medical Council that initiated the modernization of medical curricula in the UK. SSCs were proposed to make up one-third of the medical curriculum and provide students with choice, whilst allowing individual schools autonomy in how SSCs were utilized. In response, at the University of Edinburgh the undergraduate medical curriculum p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 34 publications
2
15
0
1
Order By: Relevance
“…As well as developing ethical behaviours in students, our research also found that research-based projects were seen to provide other benefits for students, such as enhanced teamwork and project management skills which could be carried into professional practice. These findings are consistent with research by Riley et al (2013) that investigated medical students' research projects. However, while it is apparent that there are positive personal gains for students who undertake study at post-graduate level related to professional and personal qualities, little is known about measurable benefits to patients, or about potential constraints that may adversely affect the ability when in practice to apply acquired knowledge and skills (Cotterill-Walker, 2012).…”
Section: Discussionsupporting
confidence: 91%
“…As well as developing ethical behaviours in students, our research also found that research-based projects were seen to provide other benefits for students, such as enhanced teamwork and project management skills which could be carried into professional practice. These findings are consistent with research by Riley et al (2013) that investigated medical students' research projects. However, while it is apparent that there are positive personal gains for students who undertake study at post-graduate level related to professional and personal qualities, little is known about measurable benefits to patients, or about potential constraints that may adversely affect the ability when in practice to apply acquired knowledge and skills (Cotterill-Walker, 2012).…”
Section: Discussionsupporting
confidence: 91%
“…Similarly, a thematic analysis of 905 SSC (Student Selected Component) projects by Murdoch-Eaton et al provided by medical students at six UK medical schools revealed gain of various research-related skills [90]. These results are also supported by eleven quantitative studies, summarized in S5 File [11,37,39,40,46,47,55,64,82,89,91]. …”
Section: Resultsmentioning
confidence: 80%
“…Four studies were carried out in the USA, 19 21 , 23 whereas 2 studies were in Canada 22 , 26 and the UK. 7 , 27 One study was done in each of the following countries: China, 34 Croatia, 10 Malaysia, 28 the Netherlands, 8 Norway, 25 and Pakistan. 24 The type of studies included cross-sectional design in 4 studies, 24 , 25 , 28 , 29 case-control design in 1 study, 19 and longitudinal cohort design in 1 study.…”
Section: Resultsmentioning
confidence: 99%
“…From a pooled analysis of the 6 studies (with 8 data sets), 20 , 23 25 , 27 , 29 the “learners’ reaction” was positive in 74% (95% CI: 60.8%–87.6%; I 2 : 97.9%) of those who were engaged in research (Figure 1 ). A pooled analysis of the 2 studies (with 3 data sets) 26 , 28 showed that 23% (95% CI: 15.5%–31.3%; I 2 : 73.8%) of the respondents were negative in response, indicating lack of interest in research activities (data not shown).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation